Are the Risk Factors for Bronchopulmonary Dysplasia and Retinopathy of Prematurity in Very Low-Birth-Weight Infants the Same? - Hui Wu; Juan Zhang; Jing Zhang; Yanhong Yu; Hua Zhang; Tongyan Han (Children)
Background/Objectives: Bronchopulmonary dysplasia (BPD) and retinopathy of prematurity (ROP) affect the prognosis of preterm infants, and their coexistence is a risk factor for poor long-term outcomes in very low-birth-weight infants. However, there has been limited in-depth assessment of common and independent risk factors for BPD and ROP within the same cohort. Therefore, we aimed to investigate the risk factors for BPD and ROP in very low-birth-weight infants born at ≤32 weeks of gestation and to explore the interaction between these two diseases. Methods: The participants were divided into four groups: BPD+ROP+, BPD-ROP-, BPD+ROP-, and BPD-ROP+. Gestational age, birth weight, maternal pregnancy complications, birth and postnatal diseases, and treatment conditions were compared among the groups. Subsequently, univariate and multivariate binary logistic regression analyses were conducted to explore the independent risk factors for BPD and ROP. Results: Common risk factors of BPD and ROP included gestational age and prolonged oxygen therapy. The multivariate analysis revealed that gestational age (OR: 4.44; 95% CI: 3–6.57), intubation resuscitation (OR: 2.35; 95% CI: 1.09–5.05), mechanical ventilation duration ≥ 7 days (OR: 1.01; 95% CI: 1.01–1.01), and prolonged total oxygen therapy (OR: 3.13; 95% CI: 1.28–7.64) were independent risk factors for BPD. Additionally, gestational age (OR: 0.66; 95% CI: 0.54–0.81) and prolonged oxygen therapy (OR: 1.02; 95% CI: 1–1.03) were independent risk factors for ROP. Conclusions: The proper control of the duration and concentration of oxygen therapy, along with the minimization of mechanical ventilation time, is crucial for reducing the incidence of both BPD and ROP.